MILLET BASED NUTRITIONAL SUPPLEMENT FOR DIARRHEAL EPISODE IN PROTEIN ENERGY MALNOURISHED CONDITION: AN EXPERIMENTAL APPROACH IN CASTOR OIL MODEL - Sachin V TEMBHURNE; Mansi S JAGDALE; Payal KATE; Ziyaurrahman AR (Arquivos de Gastroenterologia)
ABSTRACT Background: Diarrhea is a gastrointestinal transit disorder and mostly seen in malnourished children’s as per WHO report. Malnourished individuals are found to be associated with compromised immunity and lack of nutrients, which makes person susceptible to diarrhoea. Objective: For maintaining the gut health adequate and balance nutrition is essential. In this study, both fermented and non-fermented nutritional supplement was formulated and evaluated against castor-oil induced diarrhoea. Methods: Two groups of rats initially fed a 2% protein-deficient diet for ten weeks. After this period, one group received a diet enriched with nutritional components blended with fermented bovine colostrum, while the other group received a diet with non-fermented nutritional components. At the end of 20th week, castor oil was given to all animals except the control group to induce diarrhoea. Subsequently, these rats were subjected to various assessments including time of onset of the first diarrheal stool (min), faecal weight, faecal score, number of wet stools, intestinal fluid accumulation and Histopathological examination. DPPH radical-scavenging activity of nutritional blend was also determined. Results: The undernourished rats fed with non-fermented and fermented diet showed delayed the onset of diarrhea and reduction of weight stool, the decrease in the frequency and severity of defecation as well as significantly protected against the intestinal fluid accumulation as compare to negative control groups. The results showed that both the fermented and non-fermented blended composition exhibited antioxidant activity. The intestine of undernourished rats fed with fermented nutritional diet showed the absence of infiltration and improved villi structure. Conclusion: The study presents promising evidence of the potential benefits of the formulated nutritional compositions in alleviating the castor oil-induced diarrhea in undernourished wistar rats. The antioxidant activity, anti-diarrheal effects and improvements in gut histology suggest that, the nutritional compositions could be explored further as natural interventions for gastrointestinal health.